Perlindungan Konsumen atas Jaminan Keamanan Pangan dan Mutu Pangan atas Produk Makanan & Minuman oleh Pelaku Usaha Waralaba - Yosua Pasaribu, Brian Michel (UNES Law Review, 2023)
The culinary franchise industry in Indonesia is experiencing rapid growth in line with the modern era. The business has become popular because it allows for company expansion in a short period, such as in fast food franchises. Domestic and international franchises have brought much success to Indonesia. Food safety and quality policies need to be developed by fostering, developing, and improving franchising businesses. Franchise business expansion must be in line with consumer protection, ensuring the quality of products provided. Franchising opportunities are attractive for those who want to start a business with local and global franchises. Providing high standards and quality in service and sales is important, including obtaining approval from BPOM. However, not all franchise companies have obtained this accreditation. Laws have been enacted to protect consumers' rights to marketed products.